Implementasi Sistem Keamanan Rumah Berbasis Microcontroller Node MCU ESP32 dan Sensor PIR Menggunakan Telegram (Studi Kasus: Kos Putri Azzahra Serpong) - Zakaria, Hadi; Anggreyni, Ayu (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Kos Putri Azzahra is one of the boarding houses for girls in the Serpong area which was founded in 2021. Kos Putri Azzahra has 52 room units and has several facilities such as a large yard that can be used for parking motorbikes and cars. Kos Putri Azzahra has an inadequate security system so that theft of motorbikes and electronic goods from boarders often occurs. This resulted in the tenant occupancy rate decreasing dramatically and it caused a big loss for the boarding house owner. To overcome these problems, the author designs and implements an efficient security system to prevent criminal acts in the boarding environment. This system is designed using the NodeMCU Esp32-Cam Microcontroller as the main controller connected to the PIR Sensor which is placed at a strategic point in the boarding house and can be accessed remotely using the Telegram application. Data from sensors will be analyzed by NodeMCU Esp32-Cam while the Telgeram application will help to provide notifications and turn on and off sensors remotely. In this study the authors used the waterfall method to make the design flow. It is making a home security system using this PIR sensor can make it easier for boarding houses and residents to avoid theft in the boarding area. So that the occupancy rate of the boarding house can increase and there is no more theft in the Putri Azzahra boarding house area.